The Euro Area's pandemic recession: A DSGE interpretation - Roberta Cardani; Olga Croitorov; Massimo Giovannini; Philipp Ludwig Pfeiffer; Marco Ratto; Lukas Vogel (European Commission, 2021)
The COVID-19 pandemic led to a sharp contraction of economic activity in the euro area (and worldwide). Its anatomy differs strongly from other crises in recent history. We analyse the short-term economic effects of the COVID-19 shock through the lens of an estimated DSGE model. We augment the canonical DSGE set-up with 'forced savings' (lockdowns, social distancing), labour hoarding (short-time work) and liquidity-constrained firms to capture salient demand and supply effects of the COVID shock and the containment and stabilisation policies. Shock decompositions with the estimated model show the dominant role of 'lockdown shocks' ('forced savings', labour hoarding) in explaining the quarterly pattern of real GDP growth in 2020, complemented by a negative contribution from foreign and investment demand particularly in 2020q2 and a negative impact of persistently higher (precautionary) savings. The initial inflation response has been modest compared to the severity of the recession.
Keywords: C11; E1; E20; 330; COVID-19; estimated DSGE model; Euro Area; recession; forced savings